2012
DOI: 10.21608/jfds.2012.81729
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Some Additives on the Properties of Flavored With Fruit Probiotic Fermented Milk

Abstract: The effect of Glucon Delta-Lactone (GDL), disrupted Saccharomyces cerevisiae cells after freezing (DSCAF) and yeast extract (YE) on the properties of flavored with fruit probiotic fermented milk was investigated. The obtained results revealed that 5% of DSCAF activated the bacterial growth more than other additives. Therefore, it was selected to make fermented milk from UF retentate of cows' milk (14 % T.S.) with 3% ABT-4 culture. This additive accelerated the fermentation time throughout 2 hours, but GDL (0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
0
1
Order By: Relevance
“…In comparison with present study; Abou Ayana et al, [36] noticed the changes in sensory evaluation of fruity probiotic fermented milk. They showed that the total scores gradually increased in all examined treatments in the first week, and then decreased till the end of storage.…”
Section: Sensorial Evaluation: Data Incontrasting
confidence: 48%
“…In comparison with present study; Abou Ayana et al, [36] noticed the changes in sensory evaluation of fruity probiotic fermented milk. They showed that the total scores gradually increased in all examined treatments in the first week, and then decreased till the end of storage.…”
Section: Sensorial Evaluation: Data Incontrasting
confidence: 48%